Association of Polypharmacy with Colorectal Cancer Survival Among Older Patients. (20th September 2021) - Chen, Li-Ju; Nguyen, Thi Ngoc Mai; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann; Schöttker, Ben
Abstract : Background: In geriatric oncology, polypharmacy is often assessed during a comprehensive geriatric assessment. Previous studies about its association with survival among patients with colorectal cancer (CRC) were inconclusive and had high risk for indication bias. Patients and Methods: A cohort study was conducted with 3, 239 patients with CRC, aged ≥65 years, who were recruited in Germany between 2003 and 2016, while being hospitalized for CRC surgery. We defined polypharmacy as the concurrent use of five or more drugs, and excessive polypharmacy (EPP) as concurrent use of eight or more drugs. Cox proportional hazards regression models were performed to assess the associations of polypharmacy with 5-year overall (OS), CRC-specific (CSS), and non-cancer-specific survival (NCS) with rigorous adjustment for morbidity to minimize indication bias (e.g., for cancer stage, functional status, and 13 common diseases/conditions). Results: The prevalence of polypharmacy was 54.7% and that of EPP was 24.2%. During up to 5 years of follow-up, 1, 070 participants died, among whom 615 died of CRC and 296 died of other causes than cancer. EPP was statistically significantly associated with poorer up-to-5-year OS (hazard ratio [HR], 1.23; 95% confidence interval [CI], 1.02–1.47) and CSS (HR, 1.31; 95% CI, 1.03–1.68). HR point estimate for NCS was higher than 1 (1.22) but not statistically significant. Conclusion: Polypharmacy was very common and EPP was a weak risk factor for mortality in this large cohort of older patients with CRC. Clinical trials are needed to address the causality of this relationship because older patients with CRC might benefit from deprescribing drugs without an indication. Implications for Practice: The results of this study support the hypothesis that excessive polypharmacy, defined as use of eight or more concurrently used active substances, has a negative impact on the prognosis of older patients with colorectal cancer (CRC). This study suggests to oncologists that performing a medication review for older patients with CRC with eight drugs or more is indicated (especially when a broader comprehensive geriatric assessment is being performed). Such a medication review should not only focus on reducing the number of medications (by deprescribing drugs without an indication) but also check the appropriateness of indicated drugs for older patients with cancer. Abstract : Excessive polypharmacy, defined as the concurrent use of eight or more drugs, is becoming more common, especially in the older population. This article evaluates the association of polypharmacy with overall survival in large cohort patients with colorectal cancer.